How Deaf People Live: Gender, Poverty and Employment Opportunities? - Sari, Ulfi Andrian; Azharotunnafi, Azharotunnafi; Yasri, Hayyun Lathifaty (HUMANISMA : Journal of Gender Studies, 2024)
The concept of gender equality and disability long been advocated, emphasizing equal rights and equality between human beings. However, in reality, gender, disability and poverty persists as intersecting factors that contribute to discrimination against the deaf. There are stigmatising assumptions that encourage unequal treatment of the deaf. This study aims to analyse the interrelated experiences of the deaf based on gender, poverty and employment opportunities in East Java. The research method used is qualitative with a case study approach. Data were collected through observation, interviews with 29 informants, documentation and focus group discussions (FGDs). The data were analysed using the NVivo 12 software, following a series of steps: data input, coding, exploration, visualization, and presentation. The results of the study challenge the gender disability theory which suggests that women with disabilities tend to be poorer than men with disabilities. Instead, this study found that both men and women with disabilities face similar levels of poverty and encounter difficulties in accessing labour market. Some of them are poor from birth, making it difficult to get education costs and making it difficult to find work. There are also those who have difficulty getting work because they are deaf, so they lack income to meet their needs. In addition, the result supports the existence of disability-poverty cycle among the deaf. Poverty for the deaf is exacerbated by their disability, lack of health insurance, limited access to education and skills training, and difficulties in penetrating the labour market.